Similar feeding habits of two morphs of Munida gregaria (Decapoda) evidence the lack of trophic polymorphism - Perez Barros, Patricia (2010)
Munida gregaria and M. subrugosa were originally described as two different species on the basis of several morphological characters, but recent studies evidenced that both former species constitute the same biological species, so hereafter they are referred to as two morphs of M. gregaria: `gregaria' and `subrugosa'. Notwithstanding their synonimization, the occurrence of two sympatric morphs represents an interesting case for the study of the processes involved in the maintenance of these two morphotypes in nature. We hypothesized that the distinct shapes of mouthparts of both morphs may be related to different feeding habits. Adults of M. gregaria, morphs `gregaria' and `subrugosa', were collected in the Beagle Channel by epibenthic trawling during November 2004. The trophic niche of both morphs highly overlapped. Both occupied the same trophic position in the food web of the Beagle Channel, showing the same feeding habits. As predators they fed mainly on crustaceans and algae, and as deposit feeders they ingested particulate organic matter and organisms associated with the superficial layer of the sediment. However, the relative abundance of crustaceans was higher in stomachs of `subrugosa' than in those of `gregaria', a higher proportion of stomachs of `gregaria' contained more algae than in `subrugosa', and a greater frequency of occurrence of unicellular preys was found in the diet of `gregaria'. Despite these differences, this study provided no evidences to support the existence of a trophic polymorphism between morphs of M. gregaria, at least based on the feeding habit of adults.